STUDI PELAYANAN BPJS KESEHATAN MENURUT DIMENSI SERVICE QUALITY DI PUSKESMAS HALMAHERA SEMARANG TAHUN 2016 - TEGUH ARVIYANTO; SUSILO UTOMO; puji astuti (Journal of Politic and Government Studies, 2016)
The increasing number ofBPJSparticipants was not accompanied by the addition of quality healthfacilities.Puskesmas HalmaheraSemarang isone of the first-level health facilities that serveHealth BPJS patients, which is based on the data of BPJS patientsvisits, obviousthe number ofBPJSpatients tends to decrease. This study aims todescribe theservice qualityof healthBPJSaccording to the dimensions of service quality inPuskesmas HalmaheraSemarang2016. Thesample was 93 BPJS inPuskesmas HalmaheraSemarang, obtained incidental sampling. The datawere obtained using a questionnaire which was then analyzed using descriptive statistics. Theresults showed that in general the service qualityof healthBPJS according to the dimensions ofservice quality inPuskesmas Halmahera Semarang2016is a good.BPJS patienst in PuskesmasHalmaheraSemarangfeel that the reliability dimension, responsiveness dimension, assurancedimension, empathy dimension, andtangibledimensionis agood. RecommendationsforPuskesmasHalmahera Semarang isto maintain service quality dimensions that already exist, as well as fixsome things that are still classified, such as motivating nurses to be willing to spend this specialtime in communicating with patients, as well as the willingness of nurses to remind the patientsafety stuff. In addition, also need to increase the quantity and quality of medical devices in orderto complete medical equipment. Keywords: Service quality, BPJS patient